ANALYSIS OF WEEDS BIOMASS AND WINTER COVER CROPS PRIOR SOYBEAN SOWING IN SUSTAINABLE PRODUCTION SYSTEMS - Nikolić, Ljiljana; Vasiljević, Marjana; Vojnov, Bojan; Ristić, Žarko; Šeremešić, Srđan (Acta herbologica, 2025)
This study investigates the role of winter cover crops in controlling weeds within low-input and organic farming systems prior soybean sowing. Weeds are a persistent challenge in crop production, especially in organic production, requiring effective management strategies to ensure high yields, production and environmental sustainability. Traditionally, herbicides were commonly used, but growing concerns over their environmental impact have shifted the focus toward sustainable agricultural practices. The research explores the use of winter cover crops, such as rye and pea-oat mixtures, to reduce weed biomass in fields under low-input and organic farming conditions. Trials were conducted over three years in Serbia (2019-2022), the results demonstrate that cover crops significantly reduce weed biomass, with rye proving to be a strong competitor. The study highlights the potential of cover crops as an effective ecological strategy for weed management prior soybean sowing, offering benefits such as reduced herbicide use, conservation tillage, improved soil health, erosion prevention, and better long-term crop yields.